Capturing the overburden storage area construction and post-construction period in assessing the performance of alternate source control strategies - Meiers, G; Pernito, MA; Wilson, J (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
Acid and metalliferous drainage (AMD) risks are related to the geochemical characteristics of the waste rock, the physical environment in which the rock is placed and the mobilisation pathways which transport oxidation products to the receiving environment. Typical overburden storage areas (OSAs) are constructed using topdown placement with end-tipping or dozer push over a high tip face, which provides high airflow capacity and subsequently a supply of oxygen to facilitate sulphide oxidation within the waste rock. Proactive rehabilitation of OSAs focuses on reducing oxygen supply and utilises lower air permeability layers to impede advective and convective oxygen transport. This limits sulphide oxidation and the generation of stored acidity, with the desired advantage of a reduced reliance on the final cover system and/or duration for which water collection and treatment may be required. An alternative OSA construction method utilising lower air permeability layers was compared to traditional top-down construction. With the implementation of proactive rehabilitation, sulphide oxidation over the 17year construction period was reduced by 34% to 50% of the traditional top-down placement figure. Comparatively, when considering the post-construction period, there was a more substantial reduction in sulphide oxidation, with the ongoing annual rate 76% to 93% lower than traditional top-down placement. The simulated results highlight the need to assess both the construction and post-construction period in forecasting the stored and potential load of oxidation products on AMD risk reduction. The numerical simulation method which semi-couples the sulphide oxidation/oxygen consumption rate (OCR) to the in situ physical environment simulated within the modelled OSA (i.e. in situ temperature and poreoxygen concentration) provided an effective OCR generally 80% lower than the input value. Over the 26year simulation period the effective OCR reduced for the proactive rehabilitation due to the lower internal temperature and depleted oxygen, while the effective OCR increased for the traditional top-down construction in parallel with an increase in the in situ temperature and pore-oxygen concentration. The results highlight an optimised strategy for developing informative OCRs in OSA assessment.
Keywords: overburden storage area